Peningkatan Minat dan Hasil Belajar IPAS Melalui Penerapan Model Pembelajaran Kooperatif Tipe Graffiti Pada Murid Kelas IV SD Inpres Borongunti Kecamatan Bajeng Kabupaten Gowa - Azriani, Azriani; Rahman, Nawir; Nurdin, Nurdin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research is a classroom action research that aims to increase interest and learning outcomes of social studies through the application of a Graffiti type cooperative learning model in grade IV students of SD Inpres Borongunti, Bajeng District, Gowa Regency. The subject of this study is grade IV students of SD Inpres Borongunti, Bajeng District, Gowa Regency with a total of 29 students, consisting of 16 male students and 13 female students. This research was carried out in two cycles, namely cycle I which was carried out 3 meetings (the first and second meetings for the learning process and the third meeting for the assessment of science and science learning outcomes) and cycle II was also carried out 3 meetings. The two cycles were carried out for 2 months plus summarizing all existing research results. The results of the study show that the application of the Graffiti type cooperative learning model significantly increases the learning interest of grade IV students of SD Inpres Borongunti, Bajeng District, Gowa Regency. In the first cycle, the average student interest in learning only reached 69%, which reflects the need to increase student engagement and motivation to learn. However, after improvements were made in the second cycle, students' interest in learning increased sharply to 88%, indicating an increase in student enthusiasm and participation in the science and science learning process. The Graffiti type cooperative learning model has proven to be very effective in improving student learning outcomes in science subjects at SD Inpres Borongunti, Bajeng District, Gowa Regency. In the first cycle, only 51% of students achieved learning completion, while 49% of students did not complete with an average of 67.00. After the intervention in cycle II, there was a significant increase where 93% of students achieved learning completion and only 7% did not complete it with an average of 82.00. These results show that the Graffiti type cooperative learning model is able to substantially improve students' material understanding and academic achievement.